Precision medicine: Ray of hope in overcoming cancer multidrug resistance. (December 2022) - Musyuni, Pankaj; Bai, Jing; Sheikh, Afsana; Vasanthan, Kirthanashri S.; Jain, Gaurav Kumar; Abourehab, Mohammed A.S.; Lather, Viney; Aggarwal, Geeta; Kesharwani, Prashant; Pandita, Deepti
Abstract: Multi-drug resistance (MDR) developed in response to chemotherapy is one of the prominent causes of therapeutic failure. The major underlying factors that contribute to such malignancies include tumor microenvironment, genetic alterations, changes at the cellular level and most of all the heterogeneity of tumors. Recent advances in the field of oncology have prompted a mechanistic understanding of the human genome which is responsible for such alterations, upon which the therapy would be designed. Such an approach that administers drugs by targeting the molecular changes is attributed to precision medicine. Precision medicine helps design therapy as per the requirement of patients based on the sharing of similar complex tumor environments. This revolutionized approach would help in early detection, better targeting, improved patient compliance and survival along with much reduced toxicity otherwise evidenced in conventional cancer therapy. This review discusses the cause of MDR, highlighting the role of precision medicine in overcoming such critical events. Major limitations and future prospects are also highlighted. Graphical Abstract: ga1